Design and simulation automated storage and retrieval system (ASRS) using solidworks: article - Mior Hasafi, Nur Azidah Aishah (UiTM, 2020)
This paper presents the design and simulation of Automated Storage and Retrieval System (ASRS) using SolidWorks software. ASRS is a system usually used to ease the storage and retrieval of a lot of things at one place. SolidWorks is used to design the system due to the software being able to offer designers a way to design in three dimensional (3D) and provide simulation of its movements using motion analysis. It is also used to analyze critical parts in the system using Simulation Xpress study.